Profil tingkat vo2max pemain sepakbola PSCS Wijayakusuma - Ramadhan Heriyansah, Bramantio; Kurniawan, Rubbi; Pamungkas, Hari; Nidomuddin, Muhammad; Siska Sari, Reno; Widya Pradipta, Anangga (Jurnal Porkes, 2024)
VO2max reflects the level of physical fitness of an individual and is a basic asset for aspiring athletes, in addition to motivation and basic movements. The more oxygen used means the greater the aerobic capacity of an individual, enabling them to work continuously without experiencing excessive fatigue both during training and in competitions. The purpose of this study was to determine the VO2 max level of the player football team of PSCS Wijayakusuma in the age 20-24 years old. This research is descriptive Retrieval of data using survey methods with tests and measurements. The instrument used to measure the VO2 max test uses the Bleep Test. Subjects in this study are 20 football players of PSCS Wijayakusuma.The data analysis technique used in this study is quantitative descriptive analysis as outlined in the form of a percentage. The result of the research the detailed presentage of 20 football players of PSCS Wijayakusuma club show that 10% of them get excellent category, 35% of them get good category, and 55% of them get average category.